2011
DOI: 10.1364/oe.19.018707
|View full text |Cite
|
Sign up to set email alerts
|

Broadband polarization pulling using Raman amplification

Abstract: Abstract:The Raman gain based polarization pulling process in a copropagating scheme is investigated. We map the degree of polarization, the angle between the signal and pump output Stokes vectors, the mean signal gain and its standard deviation considering the entire Raman gain bandwidth. We show that, in the undepleted regime (signal input power ∼ 1 μW), the degree of polarization is proportional to the pump power and changes with the signal wavelength, following the Raman gain shape. In the depleted regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…3 (a)), the maximum PDG corresponds to the case when L c , k lf →0. As follows from the results of [8,9], fast periodic fiber spinning results in PMD mitigation and so leads to polarization pulling [7][8][9][10][11][12][13]. However, with increased frequency of amplitude modulation PDG reaches a minimum of 1.5 dB for L c = 105m and k lf = 6 km −1 and for L c = 55 m and k lf = 30 km −1 PDG reaches the maximum of 6.9 dB (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…3 (a)), the maximum PDG corresponds to the case when L c , k lf →0. As follows from the results of [8,9], fast periodic fiber spinning results in PMD mitigation and so leads to polarization pulling [7][8][9][10][11][12][13]. However, with increased frequency of amplitude modulation PDG reaches a minimum of 1.5 dB for L c = 105m and k lf = 6 km −1 and for L c = 55 m and k lf = 30 km −1 PDG reaches the maximum of 6.9 dB (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Sergeyev et al have shown that it is possible to mitigate both PDG and PMD simultaneously by using a two-section fiber ('two-section approach') in which the first section has no spin and the second one is periodically spun [5][6][7]. As follows from [7], this approach demonstrated polarization pulling of the signal SOP to the pump SOP and so can be considered as a two-section Raman polarizer which is the one of the techniques of all-optical polarization control [10][11][12][13][14][15][16]. Unlike the one-section fiber Raman polarizer demonstrated by Martinelli et al [10], Kozlov et al [11], L. Ursini et al [12] and N. J. Muga et al [13], a twosection fiber provides almost the same polarization pulling for all input signal states of polarization and so results in very small polarization dependent gain [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field research moves along three distinct paths: i) the development of linear and nonlinear methods of re-polarization of a partially coherent and initially fully depolarized light with interferometers1, in a random scattering medium4, via propagation in a Kerr medium56789, or even through propagation of a diffracting beam in free space10; ii) the engineering of dissipative polarizers1112131415161718; iii) the design of nonlinear methods of lossless polarization control of fully coherent and depolarized beams1920212223. Polarizers belonging to the first class are based on the coherent suppression of phase noise, which is intimately related to the incoherent nature of light beams.…”
mentioning
confidence: 99%
“…Moreover, it has been theoretically demonstrated that polarization pulling in a low-PMD Raman amplifier is broadband: its bandwidth extends over about 60 nm around the Raman peak Stokes shift of 13.2 THz [76]. As a result, broadband polarization attraction resulting from the combination of Raman amplification and cross-phase modulation was experimentally observed both in a few meters of isotropic fiber [23], as well as in a few km long randomly birefringent telecom fiber [77].…”
Section: Dissipative Polarizersmentioning
confidence: 99%